Β‐synuclein at the "synapse" of encephalitis and neurodegeneration in multiple sclerosis?. Issue 6 (12th June 2019) - Richman, Sarah A; Hunter, Christopher A
Abstract : Lodygin and colleagues recently identified a candidate grey matter target antigen in a rat model of multiple sclerosis, a disease classically associated with the white matter antigen, myelin.